Addressing the challenges and strategies for Western classical music in North America as a living heritage art form - Henry C.H. Shiu (International Journal of Anthropology and Ethnology)
Abstract This article proposes viewing classical music in North America as a “living heritage art form” that acknowledges the deep foundational roots of classical music, similar to how all forms of world heritage are constructed while recognizing that classical music can remain relevant within a modern cultural context. In doing so, it examines the challenges threatening the genre’s survival and proposes strategies for overcoming these obstacles. Additionally, it highlights the opportunities presented by modern technologies to support ongoing composition, performance, and public engagement, ensuring the continued appreciation and evolution of classical music in the modern era.